The entrepreneurial process grappling with the situations of interaction : the instituting modalities of the logics of proximity - Ethnographic survey of thelocal milk industry in Burkina Faso - (:unkn) unknown (My University, 2018)
Recent research in entrepreneurship field tends to give primacy to processual perspectives. However, they do not yet make it possible to understand all the situational devices that influence the located performance and the legitimacy of the entrepreneur. The point consists of studying the reality of the informal institutions whose structuring capacity is sometimes badly evaluated. For that, it was necessary to move from a rational and individual perspective of the entrepreneurship to approach it as social action dependent on the contextual injunctions. Thus, the ethnographic analysis of relations and interactions between ten mini-dairies in an African context reveals the importance of proximity logics constituting not only resources but also constraints. The mere legitimacy of formal institutions and technical objects is not always enough to offset the cost of relational isolation. Interaction is a resource that produces constraints. The performance of the agent will depend on the strategy deployed to socialize with the enabling devices.
Keywords: African Research